Studies on the toxicity of glyphosate and the effect of spermidine in conferring resistance to induced toxicity in Drosophila melanogaster - Kropf, Maximilian (Jihočeská univerzita, 2018)
In this study Drosophila melanogaster is used as a model system to study the toxicological effect of pure glyphosate. Furthermore, the ability of spermidine to confer resistance against the glyphosate-induced toxicity was also studied. Important physiological parameters were tested employing fecundity assay, lifespan measurements, and negative geotaxis assay. Protein carbonyl assay was employed in this study as a marker of oxidative stress.
Studies on the toxicity of glyphosate and the effect of spermidine in conferring resistance to induced toxicity in Drosophila melanogaster